Analisis Faktor Yang Mempengaruhi Kinerja Unit Pengumpul Zakat (UPZ) Dalam Pengumpulan Zakat Di Baznas Kabupaten Siak - Putra, Zulfadli Nugraha Triyan; Syafpawi, Syafpawi; Zulhadi, Trian (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
This study aims to analyze the factors that influence the performance of UPZ in collecting zakat at BAZNAS Siak Regency. This study uses a qualitative approach where the results of the study are expected to be the basis for solving or resolving a problem. According to the level of explanation, this study is an explanatory research where this study is conducted to find answers to why and how to a problem. The results of the study show that internal factors (policies, strategies and human resource development) have a significant influence on UPZ in collecting zakat. Likewise, external factors (public awareness to pay zakat, implementation of the Zakat Regulation, differences in public perception in paying zakat and economic conditions) influence the performance of UPZ in collecting zakat at BAZNAS Siak Regency. This study attempts to analyze in depth the factors that influence the performance of UPZ in collecting zakat at BAZNAS Siak Regency. For BAZNAS Siak Regency, this study has benefits to strengthen the performance of UPZ in collecting zakat in the work areas of each UPZ.